Bioavailability Enhancement Techniques for Poorly Soluble Drugs: A Review - Gupta, Ravi; Jain, Vidhi; Nagar, Jagdish Chand; Ansari, Aadil; Sharma, Kapil; Sarkar, Amrito; Khan, Mohd. Shahid (Asian Journal of Pharmaceutical Research and Development, 2020)
Bioavailability is defined as the rate and extent of absorption of unchanged drug from its dosage form. The oral bioavailability of drugs with poor solubility and reasonable permeability is limited by the drug dissolution step from drug products. Low aqueous solubility is the major problem encountered with formulation development of new drugs. The article briefly highlights traditional and novel techniques that are used for solubility enhancement of BCS Class II drugs are discussed in this article. The Traditional techniques include use of co-solvents, hydrotrophy, micronization, change in dielectric constant of solvent, amorphous forms, chemical modification of drug, use of surfactants etc. Novel technologies are size reduction technologies, lipid based delivery system, micellar technologies, solid dispersion and many more.